Dynamic evolution assessing of Dongsha shoal of the Radial Sand Ridges in South Yellow Sea, based on the smallest enclosing rectangle centroids method. Issue 1 (September 2020) - Liu, Binglin; Jiang, Shengnan; Zhang, Zhenke; Wu, Haotian; Wei, Guoen; Shen, Wei; Wang, Qing
Abstract: The smallest enclosing rectangle is an important parameter in the target features of geographic elements. Its centroid can indicate the general movement trend of geographic elements. Taking Dongsha in the radiant sandbar area off Jiangsu as an example, the shape was derived from long-period remote sensing images from 1973 to 2016, learning the concepts of the smallest enclosing rectangle and centroid, extract the Dongsha Shoal of each phase by ArcGIS. The smallest enclosing rectangle centroids compare the centroids of different periods to determine the overall movement trend of Dongsha Shoal in different periods. The study found that during the 43-year period, the overall movement direction of Dongsha shoal was north-north-east, specifically divided into five stages, each of which has a different direction and speed of movement. The smallest enclosing rectangle can be used as an useful method to study the dynamic change trend of marine sandbar.